2023
DOI: 10.1186/s12903-023-02878-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of access cavities on the biomechanics of mandibular molars: a finite element analysis

Abstract: Introduction This study aimed to predict the fracture resistance of a mandibular first molar (MFM) with diverse endodontic cavities using finite element analysis (FEA). Methods Five experimental finite element models representing a natural tooth (NT) and 4 endodontically treated MFMs were generated. Treated MFM models were with a traditional endodontic cavity (TEC) and minimally invasive endodontic (MIE) cavities, including guided endodontic cavity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…They claimed that the CECs preserve the mechanical stability of teeth and preserve more of the dentin as discussed by Alovisi et al (2018), Weiqi et al (2013) and Wang et al (2023). [17][18][19] That's why the working length determination without coronal flaring was used in this study as it is a way some researchers recommended and supported by some of them.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…They claimed that the CECs preserve the mechanical stability of teeth and preserve more of the dentin as discussed by Alovisi et al (2018), Weiqi et al (2013) and Wang et al (2023). [17][18][19] That's why the working length determination without coronal flaring was used in this study as it is a way some researchers recommended and supported by some of them.…”
Section: Introductionmentioning
confidence: 88%
“…14,15 The results indicated that the pre-flaring procedure provided more accurate measurements in most cases. 16 Some research studies nowadays [17][18][19] recommended the contracted endodontic cavities (CECs) that were developed from the concept of minimally invasive dentistry and provide an alternative to traditional endodontic cavities (TECs). They claimed that the CECs preserve the mechanical stability of teeth and preserve more of the dentin as discussed by Alovisi et al (2018), Weiqi et al (2013) and Wang et al (2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation